BIMBINGAN KONSELING MELALUI LAYANAN INFORMASI DALAM PROSES MENERAPKAN PROTOKOL KESEHATAN PADA MASA PANDEMI COVID-19 PADA KOPERASI UNIT DESA (KUD) MANUNGGAL JAYA - Silawati Silawati; Aslati Aslati; Windi Soraya Ferucca; Khairunnas Jamal; Mochammad Novendri S (Kutubkhanah, 2022)
Counseling guidance through information services is very much needed during the Covid-19 pandemic in implementing health protocols. The background of this research is based on information obtained from the Village Unit Cooperative officers. This research refers to how the process of information services in implementing health protocols during the Covid-19 pandemic in the Manunggal Jaya Village Unit (KUD) cooperative, Trimanunggal Village, Tapung District, Kampar Regency. The purpose of this study is to determine the process in providing these services. This research is included in the field research research, namely field research. Data collection was taken using interview, observation, and documentation techniques. This study has four (4) informants. The results of this study are that the counseling guidance through information services in implementing health protocols during the Covid-19 pandemic at the Manunggal Jaya Village Unit Cooperative (KUD) Trimanunggal Village, Tapung District, Kampar Regency is as follows: implementers prepare information to be conveyed and know the source of information so that it is more accurate, information is conveyed through discussion and through social media such as facebook and whatsapp group, make an appeal, carry out the discussion, convey information about the Covid-19 outbreak, how to prevent it and the impact if exposed to this outbreak, information is conveyed in a language that can be understood without being complicated, as well as in the implementation of the discussion, the executor invites the staff to ask questions that have not been understood.Keywords: Counseling Guidance, Information Services, Covid-19